ANALISIS YURIDIS PEMBATALAN PERJANJIAN JUAL BELI HAK ATAS TANAH - Erlina Erlina (El-Iqthisadi, 2019)
AbstractSeveral factors that resulted in the cancellation of the sale and purchase of land rights agreement were 3 (three), namely Default, Error in subject and Error in object. The procedure for cancellation of the sale and purchase agreement of land rights is 3 (three), namely the deed of deed is made by the parties, through a court decision and canceled by itself. It is expected that the parties in carrying out the sale and purchase agreement rights to the land before the Notary, must really understand the contents of the agreement that was agreed upon, so that all contents of the sale and purchase agreement can be known and understood by both parties. So that no errors occur resulting in the cancellation of the sale and purchase agreement of the land. Besides that, the contents of the sale and purchase agreement of land rights made before a Notary must be clear and firm, so that the rights and obligations of the parties to the agreement can be fair and balanced.Keywords: Cancellation of Agreement, Sale and Purchase, Land RightsAbstrakBeberapa faktor yang mengakibatkan terjadinya pembatalan perjanjian jual beli hak atas tanah ada 3 (tiga) yaitu Wanprestasi, Error in subjek dan Error in objek. Adapun prosedur pembatalan perjanjian jual beli hak atas tanah ada 3 (tiga) yaitu dibuatkan akta pembatalannya oleh para pihak, melalui penetapan pengadilan dan batal dengan sendirinya. Diharapkan para pihak dalam melakukan perjanjian jual beli hak atas tanah dihadapan Notaris, haruslah benar-benar memahami isi dari perjanjian yang diperjanjikan, sehingga semua isi perjanjian jual beli hak atas tanah tersebut dapat diketahui dan dipahami oleh kedua belah pihak. Sehingga tidak terjadi kesalahan yang berakibat pada  pembatalan perjanjian jual beli hak atas tanah tersebut. Disamping itu, isi perjanjian jual beli hak atas tanah yang dibuat di hadapan Notaris haruslah jelas dan tegas, sehingga hak dan kewajiban dari para pihak dalam perjanjian tersebut dapat adil dan seimbang.Kata Kunci : Pembatalan Perjanjian, Jual Beli, Hak Atas Tanah